Endoscopic extraction of living fasciola hepatica: Case report and literature review - Birol ÖZER; Ender SERİN and Yüksel GÜMÜRDÜLÜ and Gürden GÜR and Uğur YILMAZ and Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-